The Evolution of the Sickle Cell Anaemia in the Region of Kinshasa: a Mathematic Modelling - R.Gilles Bokolo; Cedric Musema Sinamuli; Dibere Kodondi; Bruce Shola Mafuta (Program Studi Tadris Matematika IAIN Salatiga, 2022)
We attempt to study the evolution of the sickle cell anaemia in the region of Kinshasa by proposing three models based on Markov processes. The first two models namely, the idealistic and the quasi- idealistic models fail to completely describe the data sampled. The third model, the realistic one, leads to results that match the data collected and meets the predictions of serious institutions such as the World Health Organization (about 36 percent of the population belongs to the electrophoresis categories AS or SS).